2003
DOI: 10.1007/s00234-002-0913-9
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of PICA aneurysms

Abstract: Endovascular treatment of aneurysms of the posterior inferior cerebellar artery (PICA) avoids manipulation of the brainstem or lower cranial nerves and should therefore carry a lower risk of neurological morbidity than surgical clipping. We reviewed our experience of 23 patients with PICA aneurysms treated by endovascular occlusion with Guglielmi detachable coils and documented their long-term outcome on follow-up. We observed a 28 day procedure-related neurological morbidity of 13% (3/23 patients). One patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 17 publications
2
44
0
1
Order By: Relevance
“…Among distal dissecting PICA aneurysms in the literature, the dissecting etiology has been found in 0%-80% of the cases. [15][16][17] In our cases, the etiology of the dissection was presumed to be spontaneous in 5 cases and traumatic in 1 case. The natural history of distal segment dissecting PICA aneurysms is likely different from the more common saccular aneurysms, which frequently arise at the vertebral artery-PICA junction.…”
Section: Discussionmentioning
confidence: 69%
“…Among distal dissecting PICA aneurysms in the literature, the dissecting etiology has been found in 0%-80% of the cases. [15][16][17] In our cases, the etiology of the dissection was presumed to be spontaneous in 5 cases and traumatic in 1 case. The natural history of distal segment dissecting PICA aneurysms is likely different from the more common saccular aneurysms, which frequently arise at the vertebral artery-PICA junction.…”
Section: Discussionmentioning
confidence: 69%
“…While our results do not specifically address these issues, the endovascular literature provides some insights (Table 4). 3,10,[16][17][18]21,23 The use of stents, stent-assisted coiling, or balloon-assisted coiling improves the rates of PICA preservation, but even in the largest and most recent experience selective aneurysm coiling was possible in 60 of 76 (79%) patients and the PICA was sacrificed deliberately in 11 (14%) patients. PICA occlusion was accompanied by infarcts in 6 (8%) patients, and 4 (5%) patients in the series died in hospital.…”
Section: Bypass Indicationsmentioning
confidence: 99%
“…In the study with 23 patients treated with endovascular embolization of ruptured PICA aneurysm, one author reported that procedure-related morbidity was 13% with no procedurerelated death and good outcome in 86.4% 14) . Another author reported that endovascular coiling of posterior circulation aneurysm including PICA aneurysm in 8 patients had good outcome in 77.2% 15) .…”
Section: Clinical Outcomes Of Endovascular Treatmentmentioning
confidence: 99%
“…Because of difficulty in general anesthesia due to poor general condition, recent advancement in endovascular surgery, and difficulties related with surgery, endovascular treatment is being used as a primary or alternative method for treating these aneurysms 3,6) . For ruptured or unruptured PICA aneurysms, in our knowledge, many authors 2,4,7,8,14,15) reported the clinical outcomes of surgery or endovascular treatment, but there was only one patients had the left-sided PICA aneurysms. Twelve patients had good initial H-H grade and 8 patients had poor grade.…”
Section: Introductionmentioning
confidence: 99%